Cyclodextrin-based nanosponges as drug carriers - Trotta, Francesco; Zanetti, Marco; Cavalli, Roberta (Beilstein Journal of Organic Chemistry, 2012)
Cyclodextrin-based nanosponges, which are proposed as a new nanosized delivery system, are innovative cross-linked cyclodextrin polymers nanostructured within a three-dimensional network. This type of cyclodextrin polymer can form porous insoluble nanoparticles with a crystalline or amorphous structure and spherical shape or swelling properties. The polarity and dimension of the polymer mesh can be easily tuned by varying the type of cross-linker and degree of cross-linking. Nanosponge functionalisation for site-specific targeting can be achieved by conjugating various ligands on their surface. They are a safe and biodegradable material with negligible toxicity on cell cultures and are well-tolerated after injection in mice. Cyclodextrin-based nanosponges can form complexes with different types of lipophilic or hydrophilic molecules. The release of the entrapped molecules can be varied by modifying the structure to achieve prolonged release kinetics or a faster release. The nanosponges could be used to improve the aqueous solubility of poorly water-soluble molecules, protect degradable substances, obtain sustained delivery systems or design innovative drug carriers for nanomedicine.
Keywords: controlled release; cross-linked polymers; cyclodextrin; drug delivery; nanosponges